Effects of commercial metronidazole and metronidazole benzoate suspensions on food intake in chinchillas. (1st December 2020) - Mans, C.; Fink, D.
Abstract : Objectives: To evaluate if commercially available metronidazole and metronidazole benzoate suspensions cause a reduction in food intake in healthy chinchillas and if the reduction in food intake is dose‐dependent. Materials and Methods: Twelve chinchillas were used in a randomised, controlled, blinded, complete‐crossover study. All treatments were administered orally every 12 hours for 3 days. Metronidazole (125 mg/mL) was administered at 20 mg/kg and metronidazole benzoate (25 mg/mL) was administered at 20 and 10 mg/kg. Food intake was recorded daily. The washout period between treatments was at least 14 days. Results: At 20 mg/kg PO q12h administration of both commercial suspensions resulted in a significant reduction of food intake. The greatest mean reduction in food intake occurred after 2 to 3 days of drug administration (metronidazole: −54 ± 25%; metronidazole benzoate: −44 ± 36%). After administration of metronidazole benzoate at 10 mg/kg PO q12h, the reduction in food intake was significantly less pronounced (−24 ± 36%), suggesting that negative effect of metronidazole on food intake in chinchillas is dose‐dependent. Variation in metronidazole‐induced food intake reduction differed widely between individual chinchillas. Clinical Significance: The oral administration of commercial metronidazole and metronidazole benzoate suspensions results in a dose‐dependent clinically relevant reduction in food intake in chinchillas. Metronidazole should be used cautiously in this species and food intake should be monitored during treatment. Future studies are needed in order to determine if metronidazole at 10 mg/kg q12h is an effective therapeutic dosage in chinchillas.